Synthesis of 4-amino-5-fluoropyrimidines and 5-amino-4-fluoropyrazoles from a β-fluoroenolate salt - Lucas, Tobias; Dietz, Jule-Philipp; Opatz, Till (Beilstein Journal of Organic Chemistry, 2020)
A synthesis of fluorinated pyrimidines under mild conditions from amidine hydrochlorides and the recently described potassium 2-cyano-2-fluoroethenolate was developed. A broad substrate scope was tested and mostly excellent yields were obtained. The synthesis of fluorinated aminopyrazoles from the same fluorinated precursor could be demonstrated but proceeded with lower efficiency.
Keywords: cyclization; fluorinated heterocycles; fluorine; pyrazoles; pyrimidines